2018
DOI: 10.1101/498881
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient and specific Ly6G+cell depletion: A change in the current practices toward more relevant functional analyses of neutrophils

Abstract: Neutrophils orchestrate the innate immune response against microorganisms and are increasingly recognized to modulate cancer development in primary tumors and metastases.To address their function in vivo, different approaches are used, the most common ones relying on antibody-mediated neutrophil depletion. By comparing the effects of two widely used antibodies, we demonstrate a strong efficacy but a lack of specificity for anti-Gr1. In contrast, anti-Ly6G lacks neutrophil-depletion capacity in C57BL/6 mice, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Also, how neutrophil temporal heterogeneity impacts repair of the infarcted heart remains to be determined. This will require precise, well controlled and validated timed depletion strategies (44). Gene expression manipulation using e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Also, how neutrophil temporal heterogeneity impacts repair of the infarcted heart remains to be determined. This will require precise, well controlled and validated timed depletion strategies (44). Gene expression manipulation using e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 2 days posttreatment, neutrophil counts rise again in 1A8-treated mice while it is not the case in RB6-8C5-treated mice (55). Finally, 1A8 efficiency has recently been questioned, as 1A8-treated 24 weeks old C57BL/6J mice showed no neutrophil depletion (57). The same observation was conducted with bone marrow neutrophils from BALB/c mice (58).…”
Section: Anti-ly6gmentioning
confidence: 89%
“…The same observation was conducted with bone marrow neutrophils from BALB/c mice (58). To circumvent this low efficacy, it was recently suggested that combining 1A8 treatment with a secondary antibody injection could lead to a 90% depletion of blood neutrophils (57). Nevertheless, this statement needs to be tempered since the 1A8-induced neutrophil depletion was still efficient in 9 and 24 weeks old BALB/c and FVB/N mice, and in 9 weeks old C57BL/6J mice (57).…”
Section: Anti-ly6gmentioning
confidence: 91%
See 2 more Smart Citations